Nursing informatics in nursing education - Nazlı Ulusoy, Menekşe; Uslu, Esra; Yıldırım, Alev (Innovational: Journal of Nursing and Healthcare, 2024)
Objective: In this study, it is intended to provide a conceptual framework on the nursing informatics methods used in nursing education. Method: Abstracts of articles published in the last five years with the key words "nursing informatics" and "nursing education" in Pub-Med database were screened. 46 out of 213 study abstracts were examined. Results: Nursing informatics methods used in nursing education can include the methods used in the nursing profession and those used only for training. Nursing informatics methods can take advantage of various hardware and software tools. Nursing informatics methods used in nursing education may include: The e-learning/ distance learning/ online education for use in course management systems, virtual classrooms, online tutorials. The, podcasts, database using, social software, social media, Second Life (SL), Web quest, problem-based learning integrated nursing informatics, cloud computing, e-health, information technology (IT) applications/ health informatics/ clinical information systems, road-map guided Excel VBA for formal and distance education usage. PDA-assisted simulated clinical experiences, human patient simulation, simulation scenario, electronic health records (EHR)/ electronic health records for nursing education (EHRNE) software program, tele-health applications, personal phones /smart phones, personal digital assistants / personal response systems, incident event reporting system for usage in clinical/laboratory practices. Conclusion: Actively using the nursing informatics methods in nursing education is required for aligning. There are many tools which can be used to this end.